Agile Data Architecture in Mining Industry for Continuously Business-IT Alignment: EA Perspective - Rika Yuliana; Budi Rahardjo (Department of Informatics, UIN Sunan Gunung Djati Bandung, 2018)
Data plays a vital role particularly in mining enterprises to foster innovation and business performance through precise decision-making. Scientists have created many kinds of database technology to support them, such as big data, data cloud, etc. Meanwhile business is always facing a fluctuant situation in using those various database technologies. Unfortunately, there is still hard to use database technology in a proper way because there are no model rules in making a perfect planning so that they can choose suitable tools for its own case. Therefore, this paper aims to design an agile enterprise data architecture model rules (blueprint) in mining company based on various frameworks, tools and methods/techniques so that managers can govern their data asset for sustainably business-IT alignment. This data architecture reference models can be easily adopted by CIOs in order to move toward an integrated mining enterprises as well as guide user in producing a precise decision-making.